Synthesis and cntibacterial activity of silver/montmorillonite nanocomposites - Ahmad, Mansor; Shameli, Kamyar; Darroudi, Majid; Wan Yunus, Wan Md. Zin; Ibrahim, Nor Azowa; Abdul Hamid, Azizah; Zargar, Mohsen (Medwell Publishing, 2009)
Silver nanoparticles (Ag-NPs) were successfully synthesized into the interlayer space of Montmorillonite (MMT) by chemical reduction method. AgNO3 and NaBH4 were used as a silver precursor and reducing agent, respectively. The properties of Ag/MMT nanocomposites were studied as a function of the AgNO3 concentration. The UV-vis spectra of synthesized Ag-NPs showed that the intensity of the maximum wavelength of the plasmon peaks increased with increasing AgNO3 concentration. The crystalline structure of the Ag-NPs and basal spacing of MMT and Ag/MMT were also studied by Powder X-Ray Diffraction (PXRD). The antibacterial activity of Ag-NPs was investigated against gram-negative bacteria (Escherichia coli, Escherichia coli O157:H7 and K. pneumonia) and gram-positive bacterium (Staphylococcus aureus) by disk diffusion method using Muller-Hinton Agar (MHA) at different sizes of Ag-NPs. The smaller Ag-NPs were found to have significantly higher antibacterial activity. These results showed that Ag-NPs can be used as effective growth inhibitors in different biological systems, making them applicable to medical applications such as in surgical devices.